Between autonomy of music and the composer’s autonomy. Notes on modernisms and traditionalisms in Slovenian music of the 20th century - Stefanija Leon (Muzikologija, 2006)
The aim of this article is to examine the relations between the old and the new in the context of 20th-century Slovenian music. The question about the old and the new is seen not only as a question of different facets of an age-old opposition, but also as a complex issue of the epistemological contextualization of those different facets. Centered on the main historiographical entries – the avant-garde, modernity, traditionalism, and post-modernity –, the outline of the 20th-century Slovenian musical culture endeavors to point out what is a common problem of the Western musical heritage from the past century: the problem of defining constituents of the old and the new within different epistemological contexts.